A companion to seals in the middle ages - Whatley, Laura J. (Reading medieval sources, 2019)
A Companion to Seals in the Middle Ages is a cross-disciplinary collection of fourteen essays on medieval sigillography. It is organized thematically, and it emphasizes important, often cutting-edge, methodologies for the study of medieval seals and sealing cultures. As the chronological, temporal and geographic scope of the essays in the volume suggests, the study of the medieval seal-its manufacture, materiality, usage, iconography, inscription, and preservation-is a rich endeavour that demands collaboration across disciplines as well as between scholars working on material from different regions and periods. It is hoped that this collection will make the study of medieval seals more accessible and will stimulate students and scholars to employ and further develop these material and methodological approaches to seals. Contributors are Adrian Ailes, Elka Cwiertnia, Paul Dryburgh, Emir O. Filipovi, Oliver Harris, Philippa Hoskin, Ashley Jones, Andreas Lehnertz, John McEwan, Elizabeth A. New, Jonathan Shea, Caroline Simonet, Angelina A. Volkoff, and Marek L. Wójcik.